PROFIL TINGKAT STRES PADA MAHASISWA PROGRAM STUDI S1 KEP UNIVERSITAS NEGERI GORONTALO - Jusuf, Muhammad isman (Jurnal Health and Sport, 2011)
Stess can be one ofthe social change impct and be one ofthe effect modemization usually followed by technology proliferation, migration to the city and individual competition.Among student ofwriversity, this individual competition is very incessant especiatly in the field of education and chance work. student ofuriversity is very susceptible experience stress